Microfluidics-derived microcarrier systems for oral delivery - Lijun Cai; Ning Li; Yong Zhang; Hongcheng Gu; Yujuan Zhu (Biomedical Technology, 2023)
Oral delivery is with high patient compliance but low bioavailability and controllability. The emerging microfluidics-derived microcarriers have sprung up to relieve the hurdles. Herein, a review on the recent progress in applying microfluidics-derived microcarriers for oral delivery is presented. First, we briefly introduce the microfluidic fabrication of microcarriers based on laminar flow and droplets. Then, we focus on the applications of microfluidics-derived microcarriers for oral delivery in stomach, small intestine, and colon. Last but not least, we discuss the challenges and outlooks of the microfluidics-derived microparticles for oral delivery in the end. This review is anticipated to help readers to follow up the research frontiers in this field, and guide the future development direction of microfluidics-derived microcarriers.